Sistem Informasi Manajemen Keluhan Pelanggan Hotel Menggunakan Metode Waterfall - Fauji Azwar Siregar; Muhammad Irwan Padli Nasution (STMIK Budi Darma, 2022)
Hotel Grand Istana I Syariah Padangsidimpuan is a business entity engaged in services and services. The customer service proces starts from registration and then provides services to customers according to their needs. All information relating to hotel customers who have stayed is recorded in the book. From the results of interviews, obtained the problem that often occur to hotel customers are the lack of place to submit criticism, input and suggestions to the hotel management and also the absence of feedback from hotel management to customers regarding the criticism, input and suggestion submitted. For this reason, in overcoming the problems that accur in the hotel, an information system development is carried out related to te problems that occur. Where this information system uses the waterfall methode and analysisi system used is data collection adan interviews. The implementation of this system will use PHP As programming language and MySQL as the database. The purpose of making this information system later is that customers will have a place to convey criticism, input and suggestions to hotel management and will alaso make it easier for hotel to provide information to customers so that hotel customers can increase their loyalty to the Grand Istana I Syariah Padangsidjmpuan Hotel